Etymological Study Of The Opposition “Near – Far” In The Uzbek Language - Khaitova Gulhayo Tovasharovna (Global Scientific Publishing, 2024)
To delve deeper into the etymological and theoretical aspects of the opposition “near” and “far” in the Uzbek language, it’s essential to consider broader linguistic frameworks, such as semantic fields, language contact theory, typological studies, and cognitive linguistics. This comprehensive study will allow us to understand how spatial oppositions like “near” and “far” evolve in languages, particularly within the Uzbek linguistic and cultural context
Keywords: etymology; historical linguists,; Pre-islamic roots